2009-2013 strategic plan for Le Reve Resort - Ysalina, Euckene Shayne A.; Digal, Larry N.; Concepcion, Sylvia B.; Gomez, Aurelia Luzviminda V. (Davao City School of Management, University of the Philippines Mindanao, 2008)
His study is geared towards determining the best strategy(ies) for Le Reve Resort, being in the resort industry and a monopoly resort in Makilala, Cotabato. The conceptual framework used for this study is an adaptation of both David and Pearce and Robinson's frameworks. The external analysis of the resort industry of this study covers specifically that of Regions XI and XII, considering that Le Reve Resort's customers are mostly from these regions. The result of its assessment show six (6) factors that could significantly benefit Le Reve Resort and seven (7) trends that are potentially detrimental to its position in the business. The external factor evaluation on Le Reve Resort shows that the resort's ability to respond to its external environment is deemed not satisfactory. The internal environment analysis, however, indicates seven (7) strong points and eight (8) limitations of Le Reve Resort. It was found out, through the internal factor evaluation matrix, that the resort is neither internally strong nor weak. Based on the above findings and its proposed statements of vision, mission, goals and sustainability policy, the generic strategy applicable for the resort is focus strategy which is combining overall cost leadership and differentiation to attend to the needs of its existing and potential market segments. The resulting grand strategies from SWOT and QSP Matrices suggest that the most likely strategic choice of Le Reve Resort is product development, followed by market penetration, turnaround strategy and lastly, sustainability strategy. The marginal gap between the attractiveness score of each alternative means that they can be implemented simultaneously, but subject to various considerations, especially the capital requirement. In order to know what Le Reve Resort must do well to effectively implement the above-mentioned strategies, this paper used the balanced scoreboard by Kaplan and Norton, indicating the goals per perspective, measure and specific targets. Moreover, the proposed policy guidelines per component and per functional area were made to ensure effective implementation of the proposed actions. The traditional and contemporary approaches to strategic controls were also distinguished to emphasize the equal importance of monitoring both the internal and external environment to determine whether there will be a need to modify some or all strategies.
Thesis, Graduate(Master in Management)--University of the Philippine Mindanao, December 2008
Keywords: Strategic plan